The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/aem.71.9.5341-5347.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Arbuscular-Mycorrhizal Fungi on Their Plant Host for Palmitic Acid Synthesis

Abstract: Lipids are the major form of carbon storage in arbuscular-mycorrhizal fungi. We studied fatty acid synthesis by Glomus intraradices and Gigaspora rosea. Our data strongly suggest that the fatty acid synthase activity of arbuscular-mycorrhizal fungi is expressed exclusively in the intraradical mycelium and indicate that fatty acid metabolism may play a major role in the obligate biotrophism of arbuscular-mycorrhizal fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 35 publications
4
122
1
Order By: Relevance
“…AM fungi store and transport most of their carbon in the form of lipids [9][10][11][12]. However, AM fungi cannot produce the basic fatty acid (FA) palmitate (C16) in the absence of their host (as shown in two distantly related species, Rhizophagus irregularis and Gigaspora rosea), while FA elongation and desaturation can occur independently of the plant [13]. This and similar results suggested that AM fungi can only synthesize C16 in the IRM [3,13].…”
Section: Lipid Metabolism In Am Fungi -Open Questions and Surprisesmentioning
confidence: 57%
See 2 more Smart Citations
“…AM fungi store and transport most of their carbon in the form of lipids [9][10][11][12]. However, AM fungi cannot produce the basic fatty acid (FA) palmitate (C16) in the absence of their host (as shown in two distantly related species, Rhizophagus irregularis and Gigaspora rosea), while FA elongation and desaturation can occur independently of the plant [13]. This and similar results suggested that AM fungi can only synthesize C16 in the IRM [3,13].…”
Section: Lipid Metabolism In Am Fungi -Open Questions and Surprisesmentioning
confidence: 57%
“…Given the absence of the FAS-I complex from AM fungi, and the fact that lipids are the main storage form of carbon in AM fungi, the transfer of lipids from the plant to the fungus would circumvent the metabolically inefficient conversion of sugars to FAs through glycolysis, pyruvate decarboxylation, and the mitochondrial FAS-II pathway in the IRM of the fungus. However, Trépanier and colleagues have refuted the transfer of C16 from the plant to the fungus based on the fact that the relative labeling of fungal FAs (vs plant FAs) was >10-fold higher when mycorrhizal roots were supplemented with labeled sucrose versus when they received labeled acetate [13]. Because the conversion of sucrose to FAs in the plant would require a transition through acetyl-CoA, it would be expected that a similar level of labeling should be generated with both sucrose and acetate if the FAs were produced in the plant and transferred to the fungus[…”
Section: Non-membrane Lipid Functions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperforin biosynthesis in H. perforatum starts from amino acid precursors and proceeds with prenylation (Karppinen et al 2007). It has been shown that AMF can decrease free amino acid content and saturated fatty acid content in host plants (Rivero et al 2015;Saia et al 2015b) and that AMF depend on their host plants for the biosynthesis of some special fatty acids (Trepanier et al 2005). Hence, it is likely that hyperforin biosynthesis decreases in mycorrhizal rather than in control plants due to a sequestration of precursors needed by the AMF.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread occurrence of AM symbioses today (Smith and Read, 2008) indicates that they continue to play key roles in terrestrial ecology. Growth and spore development of AM fungi depends on successful colonization of roots to access plant carbohydrates and convert them into fatty acids and other compounds (Solaiman et al, 1999;Trépanier et al, 2005). In return, AM fungi take up minerals, especially Pi, from the soil and deliver them to their host plants (Marschner and Dell, 1994).…”
Section: Introductionmentioning
confidence: 99%